Constraining the local burst rate density of primordial black holes with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Caballero-Mora, K. S.; et al. (Journal of Cosmology and Astroparticle Physics, 2020)
Primordial Black Holes (PBHs) may have been created by density fluctuations in the early Universe and could be as massive as > 109 solar masses or as small as the Planck mass. It has been postulated that a black hole has a temperature inversely-proportional to its mass and will thermally emit all species of fundamental particles via Hawking Radiation. PBHs with initial masses of ∼ 5 × 1014 g (approximately one gigaton) should be expiring today with bursts of high-energy gamma radiation in the GeV-TeV energy range. The High Altitude Water Cherenkov (HAWC) Observatory is sensitive to gamma rays with energies of ∼300 GeV to past 100 TeV, which corresponds to the high end of the PBH burst spectrum. With its large instantaneous field-of-view of ∼ 2 sr and a duty cycle over 95%, the HAWC Observatory is well suited to perform an all-sky search for PBH bursts. We conducted a search using 959 days of HAWC data and exclude the local PBH burst rate density above 3400 pc-3 yr-1 at 99% confidence, the strongest limit on the local PBH burst rate density from any existing electromagnetic measurement.
CRIS-Team Scopus Importer:2020-05-22